2019
DOI: 10.1186/s12889-019-7670-8
|View full text |Cite
|
Sign up to set email alerts
|

Addressing context to understand physical activity among Muslim university students: the role of gender, family, and culture

Abstract: BackgroundPhysical inactivity is a crucial risk factor for the development of chronic health issues, which have a high incidence among Arabs living in the Gulf Cooperation Council (GCC) countries. The Qatar Stepwise Survey 2012 reported that approximately 44% of young adults 18–44 years of age had insufficient levels of physical activity. Family is a powerful source of information and socialization for adolescents and has a strong influence on their attitudes, decision-making, and behaviors.MethodsThe purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 19 publications
3
28
1
Order By: Relevance
“…This could be said that some parents give priority to high academic involvement and achievement without considering the crucial role that LTPA could play in enhancing children's mental ability. This is similar to the study conducted by Aljayyousi et al (2019) who found that some students mentioned that their families give priority to work, personal and family commitments, and academic achievement over physical activity. Yao and Rhodes (2015) concluded that the relationship between father-son PA modeling was higher than mother-son PA modeling, yet the findings were similar for the relationship between mother-daughter and father-daughter PA modeling.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This could be said that some parents give priority to high academic involvement and achievement without considering the crucial role that LTPA could play in enhancing children's mental ability. This is similar to the study conducted by Aljayyousi et al (2019) who found that some students mentioned that their families give priority to work, personal and family commitments, and academic achievement over physical activity. Yao and Rhodes (2015) concluded that the relationship between father-son PA modeling was higher than mother-son PA modeling, yet the findings were similar for the relationship between mother-daughter and father-daughter PA modeling.…”
Section: Discussionsupporting
confidence: 89%
“…In their meta-analysis, Yao and Rhodes (2015) concluded that the relationship between father-son was higher than that of mother-son modelling, while the same occurred between motherdaughter and father-daughter. Aljayyousi et al (2019) indicated that some students highlighted that their families give priority to work, personal commitments and academic achievement over involvement in PA. They added that father spend long hours at work and the mother would take care of family members and doing housework, which negatively impacted physical activity time and choices.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the parents revealed that boys were much more likely to be involved in sport and that girls were more likely to grow disinterested as they become older. The parents also communicated the lack of serious opportunities for continuous engagement in sports in schools, especially in Islamic schools, in particular for girls and older adolescents [ 71 ]. This was corroborated by the frustration that was expressed by adolescent girls regarding a lack of sporting initiatives and the experience of being denied access to sports facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of motivation, limited free time, fear of falling, cost, transportation, pain, and lack of enjoyment are seen as barriers to participating in regular PA (20)(21)(22). A report from Kenya found associations between low levels of PA and the demographic and social changes that prevail there (23). However, no previous work has specifically looked into the PA patterns and the factors that predict PA among the urban population in Odisha state of India.…”
Section: Introductionmentioning
confidence: 99%